2005
DOI: 10.1159/000086779
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Nuclear Morphometry at the Invasive Front of T1 Colorectal Cancer and Relation to Expression of VEGF-A and VEGF-C

Abstract: Objectives: To better understand the metastatic potential of T1 colorectal cancer, we investigated variations in nuclear morphometry and expression of angiogenic factors in cancer cells at the invasive front. Sixty-five patients who had undergone curative resection were entered. Methods: Nuclear shape factor, area, width, and proportion of cells with large nucleoli in all cells were determined in two high-power magnification areas at the invasive front of the tumor. We then performed the Ward method for cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…Some reports described a strong relationship between expression of VEGF-C and lymph node metastasis in T1 colorectal cancer [12]. In our study, in which T3 rectal cancer was studied, the degree of expression of VEGF was very high regardless of lymph node metastasis status.…”
Section: Discussionsupporting
confidence: 44%
“…Some reports described a strong relationship between expression of VEGF-C and lymph node metastasis in T1 colorectal cancer [12]. In our study, in which T3 rectal cancer was studied, the degree of expression of VEGF was very high regardless of lymph node metastasis status.…”
Section: Discussionsupporting
confidence: 44%
“…Possible risk factors for lymph node metastasis in submucosal invasive colorectal carcinoma include the depth of submucosal invasion, poorly differentiated histology, lymphatic vessel invasion, expression of vascular endothelial growth factor-A and -C, and expression of β-catenin (Takayama et al 1998;Maeda et al 2003;Kojima et al 2005;Walgenbach-Bruenagel et al 2006;Liang et al 2006;Saad et al 2006;Kaneko et al 2007a;Ishii et al 2009). Several studies have reported that tumor budding is a histological risk factor for lymph node metastasis of colorectal carcinoma (Hori et al 2005;Park et al 2005;Masaki et al 2006;Kaneko et al 2007b).…”
mentioning
confidence: 99%
“…The attempt to measure nuclear morphologic changes as an effect of DNA alterations has characterized the studies of several investigators during past decades. [3][4][5][6][7][8][9][10][11][12][13][14][15][16]19 Some of the authors claimed that quantitative morphometric analysis has the capability of measuring nuclear-related variables with objectivity. 11,13,20 Furthermore, it has been reported that morphometric analysis could improve the prediction of prognosis for several malignancies, including carcinomas of the ovary, 21 breast, 22 thyroid, 23 kidney, 24 bladder, 25 stomach, 26 and colon-rectum.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] More recently, some studies supported a possible role for nuclear morphometry measurements of nuclear area and nuclear shape in predicting colorectal carcinoma survival. [5][6][7][8][9][10][11][12][13][14][15][16] However, a comparison of these studies highlights several inconsistencies. Large nuclear area has been associated with worse outcome, [10][11][12][13][14]16 as well as with better outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation